Dimensional Tolerances for Additive Manufacturing: Fused Deposition Modeling - Knoop, Frederick; Lieneke, Tobias (Inside 3D Printing 2017)

Geometrische Toleranzen für additive Fertigungsverfahren - Lieneke, Tobias; Denzer, Vera; Zimmer, Detmar (3. Summer School Toleranzmangement 2017)

Kombination etablierter und additiver Fertigung: Wirtschaftlicher Einsatz des Laser-Strahlschmelzens (LBM) durch die Kombination mit etablierten Fertigungsverfahren in einer Prozesskette - Eschner, Niclas; Kopf, Robin; Lieneke, Tobias; Künneke, Thomas; Berger, Dietrich; Häfner, Benjamin; Lanza, Gisela; Zimmer, Detmar (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Der Serieneinsatz der additiven Fertigung ist maßgeblich durch die hohen Kosten und der geringen Produktivität der Verfahren limitiert. Der hier vorgestellte Ansatz zeigt, wie die Wirtschaftlichkeit des Laser-Strahlschmelzens (LBM) durch die Kombination mit etablierten Fertigungsverfahren erhöht werden kann. Ziel ist es, nur solche Funktionsträger additiv zu fertigen, die einen höheren Kundennutzen bringen. Dazu werden Konstruktionsrichtlinien definiert, Prozessketten erarbeitet und eine Qualitätssicherung mittels Ultraschallüberwachung realisiert.

Rational Decision-Making for the Beneficial Application of Additive Manufacturing - Deppe, G.; Koch, R.; Kaesberg, M. (28th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing is a technology that offers a high potential forindustrial companies.Nevertheless, companies lack experience with this new technology and face the problem to identify processes where a successful and beneficial application can be achieved. They have to be supported in this analysis with a decision support tool which is capable to compare different manufacturing or repair approaches in order to determine the optimal solution for the correspondent use case. This is not always driven solely by costs but can also be critically affected by further influencing factors. This is why the decision support takes into account also time and quality alongside the costs. For a time-critical spare part supply, for example within aerospace sector, they are substantial for taking a decision. The presented decision support features a multi-attribute decision-making approach for selecting the most appropriate process, either Additive Manufacturing, conventional technologies or an external procurement.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Integrating AM into existing companies - selection of existing parts for increase of acceptance - Kruse, A.; Reiher, T.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In many branches in the designengineerdepartment, product designs are just variations of existing parts. To bring the additive manufacturing technology closer to the Designer, it is necessary to show them which of their existing, conventionally manufactured parts can be produced with this technology. Apartselection methodology supportsdesigners in the decision whether a part is suitable for additive manufacturingor not. Due to the potential of the technology, which was especially seen in the aerospace industries, many criteria of the methodology were initially adapted for this industry. Furthermore the methodology is based on a quantified weighting system, which comes to a certain subjectivity. For future use, a development towards a less subjective methodology should be accomplished. Through a more detailed adaption for individual industries and a simplification of the input mode, the objectivity of the criteria can be increased. Likewise, the input time can be reduced by simplifying the questioning. A more efficient part selection will be achieved by a better weighting system.In the BMBF project “OptiAMix” this methodology is supposed to be further developed for highly different branches. By a better weighting system, the part selection will be more efficient. Therefore,the willingness for the use of the improved selection andfor the additive manufacturing technology will be increased.

Design for protection: Systematic approach to prevent product piracy during product development using AM - Jahnke, U.; Koch, R.; Oppermann, A. T. (28th Annual International Solid Freeform Fabrication Symposium)
Although infringements of intellectual properties in terms of product piracy are growing for years and threaten investments in research and development most companies still rely on legal measures like property rights. A more preventive effect to protect against counterfeits can be achieved using technical measures complicating reverse engineering, improving traceability and assuring data protection. Additive Manufacturing can contribute a lot to the effectivity and efficiency of those technical measures but presently they are often unconsidered during product development. To support decision makers and designers through all the steps of a product development process an integrated systematic approach has been developed. Protective measures using AM are allocated to specific process steps and responsible persons in charge so that the result is a guideline for “design for protection”. The main idea is to help developing piracy-robust products for that the return of investment is not threatened by counterfeits and its economical impacts.

Ramp-Up-Management in Additive Manufacturing – Technology Integration in existing Business Processes - Büsching, J.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
In conventional manufacturing, ramp-up-management describes the planning and organization of the period between finished product development and the achievement of full production capacity for defined products. This classification has to be adapted and restructured by means of product independent and tool-free production in additive manufacturing. Therefore ramp-up-management already starts with decisions on the extentof the use of additive manufacturing, includes the building of technology-know-how as well as the technology integration into processes and infrastructure of the company and ends with the attainment of a sufficient process reliability for the AM-machine. This paper focuses on technology integration in processes and infrastructure, which is part of the German research project OptiAMix. In this project, new systems for process state analysis adapted to additive manufacturing and methods for the optimal integration of additive manufacturing are developed. Furthermore ways of using the synergies of existing infrastructures and new innovative production technologies are determined.

Computer integration for geometry generation for product optimization with Additive Manufacturing - Reiher, T.; Vogelsang, S.; Koch, R. (28th Annual International Solid Freeform Fabrication Symposium)
Designing parts for additive manufacturing (AM) offers a broad range of geometrical and functional potentials. On the one hand the manufacturingtechnology offers the possibility of manufacturing highly complex freeform shapes, often referred to as bionic shapes. By use of these, perfect force fluxes without stress risings due to imperfect notches are realizable, getting the most value of used material. On the other hand these complex structures require a reliable geometry representation in compatible CAD-files. Conventional CAD systems were developed to generate geometries that are manufacturable with conventional machining. These are not capable of representing the high complex designs for AM. Especially for geometries generated by CAE like from topology optimization the conventional CAD systems fail to take advantage of the combination of CAE and AM. This paper explains why there is a lack of compatibility of well-known CAD systems with the potentials of AM. Therefore the AM-side of the problem is described by showing some potentials of AM and the need of high complex structures for this manufacturing technology. For the other side of the problem conventional methodologies for geometry representation of CAD systems are described and their limitations with regard to AM are worked out. Finally a voxel based geometry representation is presented as a solution for computer aided geometry generation of high complex AM–structures.

Hybrid Manufacturing with Additive Manufacturing - Deppe, G.; Lindemann, C. (CECIMO Magazine)
Additive Manufacturing provides an outstanding technological and economic potential for a wide range of industries. Particularly in the field of small series production with many product variants, the technology offers decisive advantages, such as reducing component weight, functional integration, complex parts or individualization. Today potential users struggle with the integration of this technology in their businesses. The production costs of this technology often seem too high compared to traditionally manufactured parts and many users seem disappointed with the performance of the technology. The reasons for that are manifold, but often Additive Manufacturing is considered only as an isolated technology.

Holistic approach for industrializing AM technology - from part selection to test and verification - Reiher, T.; Lindemann, C.; Jahnke, U.; Deppe, G.; Koch, R. (Progress in Additive Manufacturing)
Even in times where additive manufacturing has a peak in media and industry interest, only few companies have already implemented this technology. Many companies struggle with the use of AM even if they have already identified the benefits of this technology for their business. Additional knowledge along the whole product development chain is necessary to succeed in implementing this technology. As all other production technologies, AM has certain strength and weaknesses which affect the suitable part candidates. Redesign or manufacturing approaches of unsuited part candidates are no very likely to be successful. In general, aspects like design rules need to be known along the product development process in order to achieve technology-based benefits during production and post-processing resulting in economic success. This paper will present a holistic approach which will assist the designer during product development and manufacturing based on an example part from the space industry. Then methodology starts with an appropriate part selection as a key parameter for the product development process. Based on the promising part candidates, deductions for the further product development process will be described. This includes approaches for functional integration as well as a methodology for the compilation of part requirements. Those are utilized for a black box methodology, ensuring a time-efficient redesign based on FEA optimization and design rules for additive manufacturing. Best practices for integrating (or in the best case avoiding) traditional technologies are discussed. Based on this, the development of industrialization and test and verification plans for production are shown. This includes the marking of parts for traceability during the whole product lifecycle for quality reasons as well as for product protection. Furthermore, production and production planning are discussed. This is followed by post-processing and testing procedures of the part. The paper will close with a detailed economic view on the topic and some deductions regarding the changes in the supply chain. The methodology itself is discussed and explained on a real sample metal part. The general methodology is discussed on the basis of the space industry but is subject to be adapted to other industries.

Reproduzierbarkeit der Maßhaltigkeit im Fused Deposition Modeling - Knoop, F.; Lieneke, Tobias; Schöppner, Volker (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
Fused Deposition Modeling (FDM) is used for prototypes, single-partproduction and small batch productions of thermoplastic components. This manufacturing technique has the huge benefit that no forming tool is needed. The knowledge about dimensional deviations which occur in the FDM process is necessary for calculating fits and for determining tolerances. A major challenge is the reproducibility of the dimensional accuracy of FDM parts and the reproducibility between different FDM machines. There are many influential factors on the dimensional accuracy in the FDM process for example geometric, material-specific or process-specific factors, which are considered in this paper. The influence of the part position on the build platform of a Stratasys Fortus 400mc is analyzed in terms of the achievable dimensional accuracy. For this purpose, the temperature distribution in the actively heated build chamber is investigated and possible correlations to the dimensional accuracy are identified. The reproducibility of one machine is examined by a multiple production of the test specimens. In addition, a comparison with three other FDM machines from Stratasys is made. Afterwards, the long-term reproducibility of the dimensional accuracy is verified to consider how environmental influences such as maintenance or modification of machine components affect the dimensional accuracy of the FDM process.

Considering machine- and process-specific influences to create custom-built specimens for the Fused Deposition Modeling process - Schumacher, C.; Schöppner, Volker; Guntermann, J. (28th Annual International Solid Freeform Fabrication Symposium)
Compared to conventional polymer processing technologies the material selection in the Fused Deposition Modelling (FDM) process is restricted. To expand the range of materials the requirements for the material properties and the semi-finished products (filaments) must be clarified. For this, a machine- and process-independent rating of the processability is necessary. The established standards for the tensile strength test apply to specimens with nearly isotropic mechanical properties. The FDM process generates anisotropic parts. The properties are mainly influenced by the machine quality and the data processing. It is not possible to test a material for FDM independently of the machine and the data processing. In this paper, machine and process specific influences are investigated. Considering these influences, a custom-built specimen is created to test the tensile strength of the welding seams for polyamide 6. This procedure allows a machine- and process-independent rating of the processability in terms of tensile strength for different materials.

Geometrical Accuracy of Holes and Cylinders Manufactured with Fused Deposition Modeling - Knoop, F.; Schöppner, Volker (28th Annual International Solid Freeform Fabrication Symposium)
A widely used Additive Manufacturing (AM) technology is Fused Deposition Modeling (FDM) to create prototypes and end-use parts with close-to-production thermoplastics. For their use as a final product, it is necessary that additively manufactured parts strictly adhere to the geometrical requirements of the technical drawing. In this paper, the holes and cylinders of the cylindrical elements are investigated in terms of achievable geometrical accuracy. For this purpose, different test specimens that allow a measurement of inner and outer diameters from 3 to 80 mm were designed. All specimens were measured with a coordinate measuring machine (CMM) to evaluate deviations from the nominal dimension and form deviations. The measuring method includes a scanning of the surface to record the course of dimensional deviations over the diameter. Thus, it was possible to visualize how deviations on cylindrical elements manufactured in FDM occur. In order to counteract these deviations and to improve the dimensional accuracy, different shrink factors and filling patterns were investigated. Consequently, an improvement of the dimensional accuracy was achieved.

Beurteilung der Schweißnahtfestigkeiten verschiedener Kunststoffe im FDM-Prozess - Schöppner, Volker; Schumacher, C.; Guntermann, J. (Jahresmagazin Kunststofftechnik)
Um die Materialauswahl für den FDM-Prozess zu steigern, sollten die durch den FDM-Prozess an das Material gestellten Anforderungen bekannt sein. Dazu ist eine von der Maschine und der individuellen Datenaufbereitung möglichst unabhängige Bewertung der FDM-Verarbeitungseignung wünschenswert. In diesem Artikel werden eine Prüfmethode und ein dazu entwickelter Probekörper vorgestellt, mit dem die Schweißnahtfestigkeit verschiedener Polyamid 6 Typen im FDM-Prozess ermittelt und verglichen wird.

Universal Micromachining Platform and Basic Technologies for the Manufacture and Marking of Microphysiological Systems - Moritzer, Elmar; Hirsch, André; Günther, K.; Sonntag, F.; Klotzbach, U.; Lasagni, A.F. (Micromachines)
Micro Physiological Systems (MPS), also known as Multi-Organ-Chip, Organ-on-a-Chip, or Body-on-a-Chip, are advanced microfluidic systems that allow the cultivation of different types of cells and tissue in just one common circuit. Furthermore, they thus can also adjust the interaction of these different tissues. Perspectival MPS will replace animal testing. For fast and flexible manufacturing and marking of MPS, a concept for a universal micromachining platform has been developed which provides the following latest key technologies: laser micro cutting of polymer foils, laser micro- and sub-micro-structuring of polymer foils, 3D printing of polymer components as well as optical inspection and online process control. The combination of different laser sources, processing optics, inspection systems, and print heads on multiple axes allows the change and exactly positioning to the workpiece during the process. Therewith, the realization of MPS including 3D printed components as well as direct laser interference patterned surfaces for well-defined cell adhesion and product protection is possible. Additional basic technologies for the generation of periodical line-like structures at polycarbonate foils using special Direct Laser Interference Patterning (DLIP) optics as well as for the 3D printing of fluid-tight cell culture reservoirs made of Acrylonitrile Butadiene Styrene directly onto polycarbonate microfluidics were established. A first prototype of the universal micromachining platform combining different lasers with Direct Laser Writing and DLIP is shown. With this laser micro cutting as well as laser micro-structuring of polycarbonate (PC) foils and therewith functionalization for MPS application could be successfully demonstrated.

Fatigue Behavior of FDM Parts Manufactured with Ultem 9085 - Fischer, M.; Schöppner, Volker (JOM: The Journal of The Minerals. Metals & Materials Society (TMS))
The mechanical characterization of fused deposition modeling (FDM) parts is mostly done by static tests. In many applications, parts are also dynamically loaded. Here, fatigue tests can help to identify the expected lifetime of a part. This article discusses the fatigue behavior of FDM specimens manufactured with Ultem 9085. For this, tensile bars are manufactured according to ASTM D638 in different build orientations. Tests are performed in a range of pulsating tensile stresses, and S-N curves are documented for different build orientations. For higher loads, the FDM anisotropy characterizes the lifetime of used specimens, which is similar to static tensile bars. For lower loads, including a higher number of cycles to failure, S-N curves of different build orientations converge. In further tests, tensile bars were chemically smoothed with chloroform vapor. Chemical smoothing reduces surface roughness and increases tensile strength of specimens in the upright build direction. Fatigue tests of chemically treated specimens show no significant lifetime increase.

Quality Improvement of FDM Parts by Parameter Optimization - Knoop, F.; Kloke, A.; Schöppner, Volker (32nd International Conference of the Polymer Processing Society)
Fused Deposition Modeling (FDM) is an Additive Manufacturing (AM) technology which is used for prototypes, single-part-production and also small batch productions. For use as a final product, it is important that the parts have good mechanical properties, a high dimensional accuracy and smooth surfaces. The knowledge of the mechanical properties is very important for the design engineer when it comes to the component design. In this paper, investigations were conducted with the polymer ABS-M30 from Stratasys Inc. To achieve a quality improvement of FDM parts, various toolpath parameters and orientations were used. Within the mechanical properties, the tensile, flexural and impact strength were evaluated. Furthermore, the tensile strength of FDM parts is compared to injection molded specimens. With optimized parameters, an increase of the tensile strength by up to 28 % and a doubling of the impact strength were possible.

Untersuchung der Werkstoff-, Prozess- und Bauteileigenschaften beim Fused Deposition Modeling Verfahren - Kloke, Agnes
In dieser Arbeit wurde ein Prozessverständnis für das FDM-Verfahren hinsichtlich der Verarbeitung des Materials Ultem*9085 aufgebaut. Es wurde der Einfluss des Materials, des Prozesses und der Maschine auf die resultierende Bauteilqualität untersucht. Die Materialqualität unterschiedlicher Chargen zeigt, dass Feuchtigkeit im Material die Strangablage beeinflusst. Die Analyse der Prozessparameter, die anhand der Kurzzeitfestigkeiten analysiert wurden, zeigt einen starken Einfluss der Aufbauorientierung. Mittels einer Parameteroptimierung können ferner gleiche Festigkeitswerte wie aus dem Spritzgießprozess erreicht werden. Bei der Untersuchung der Langzeitfestigkeiten wurde festgestellt, dass sich die Festigkeitswerte bei unterschiedlichen Umgebungsbedingungen nicht ändern. Die Untersuchung einiger Anlagenkomponenten auf die resultierende Oberflächengüte, Geometriegenauigkeit und Festigkeitseigenschaften kann den Einfluss von u. a. der Bauraum- sowie der Düsentemperaturen auf die Bauteilqualität zeigen. Zuletzt wurde die Möglichkeit einer Leichtbauanwendung anhand von Sandwich-Prüfkörpern untersucht. Hierbei beeinflussen sowohl die verfahrensunabhängige Mechanik als auch die verfahrensspezifischen Effekte die Festigkeitswerte.

Manufacturability and Mechanical Characterization of Laser Sintered Lattice Structures - Josupeit, Stefan; Delfs, Patrick; Menge, Dennis; Schmid, Hans-Joachim (27th Annual International Solid Freeform Fabrication Symposium)
The implementation of lattice structures into additive manufactured parts is an important method to decrease part weight maintaining a high specific payload. However, the manufacturability of lattice structures and mechanical properties for polymer laser sintering are quite unknown yet. To examine the manufacturability, sandwich structures with different cell types, cell sizes and lattice bar widths were designed, manufactured and evaluated. A decisive criterion is for example a sufficient powder removal. In a second step, manufacturable structures were analyzed using four-point-bending tests. Experimental data is compared to the density of the lattice structures and allows for a direct comparison of different cell types with varied geometrical attributes. The results of this work are guidelines for the design and dimensioning of laser sintered lattice structures.